The specific nature of environmental damage and the 'conventionality' of its assessment as factors hindering the development of environmental insurance in the Russian Federation - Boltanova, Elena S. (Asia Pacific journal of environmental law)
This examination of Russian legislation and jurisprudence on compensation for damage to natural resources (environmental damage) concludes that this type of liability is regulated haphazardly. Despite clarification by the highest courts on preference of in-kind recovery, the fiscal approach prevails. In 99 percent of cases supervisory authorities sue the polluter for monetary compensation for damage in order to replenish the federal or local budget. Defendants are often limited in their right to offset costs incurred in remediation. Uncertainty in resolving a number of practical issues related to the consequences of pollution misleads businesses and reduces the attractiveness of this sector for insurers. In order to create legal prerequisites for the development of environmental insurance, some legislative changes are proposed. First, it is recommended that Chapter 59 of the Russian Civil Code ('Obligation to compensate for harm') be supplemented with provisions on liability for pollution. Next, it is necessary to define the key rules of environmental damage compensation: to name components of this damage; to emphasize the priority of recovery measures insofar as the tortfeasor proves the ability to restore natural resources; to secure the tortfeasor's right to offset necessary costs incurred to remediation. Finally, in case of introduction of compulsory environmental liability insurance, it is advisable to specify the in-kind form of insurance compensation as the main one, that is, the insurer's obligation to finance the costs of pollution remediation and restoration measures.